Spójność polskiego systemu wspierania umiędzynarodowienia działalności małych i średnich przedsiębiorstw w latach 2007–2013 – ocena i rekomendacje na nową perspektywę finansową 2014–2020 - Justyna Kulawik-Dutkowska (Studia i Materiały)
The aim of this article is to describe the system of support of SMEs’ internationalization, assess its strengths and weaknesses and develop recommendations for the future, in particular with regard to the new multiannual financial perspective 2014 – 2020. System of support of SMEs’ internationalization is very complex, it encloses direct support instruments addressed to entre- preneurs implemented at EU, national and regional level, especially through Structural Funds, indirect support instruments, such as services provided by business support organisations and public support addressed to these institutions. Measures supporting directly Polish entrepre- neurs’ business activities abroad and those supporting development of innovative activities of companies contributing to improvement of their competitiveness at the international markets could also be mentioned. Author will attempt to assess the functioning of the system, in parti- cular with regard to its coherence. It will be mainly based on analysis of the strategic and pro- gramming documents, review of instruments of support and analysis of activities of institutions engaged in supporting the SMEs’ internationalization. Based on the assessment, recommenda- tions regarding improvement of the system will be issued which could provide a starting point for the discussion on a possibility to introduce changes in 2014–2020 perspective.